The effects of various retention factors on the choice of where rural origin Umthombo Youth Development Foundation health science graduates work - Richard Gavin MacGregor; Andrew Ross (James Cook University, 2024)
Introduction: South Africa has an inequitable distribution of health workers between the public and private sector, with rural areas being historically underserved. As rural background of health workers has been advocated as the strongest predictor of rural practice, the Umthombo Youth Development Foundation (UYDF) has invested in recruiting and training rural-origin health science students since 1999 as a way of addressing staff shortages at 15 district hospitals in northern KwaZulu-Natal Province, South Africa. UYDF's intervention is to support students to overcome their academic, social, and economic challenges and expose them annually to rural health practice. This study investigated the effects of various retention factors on the choice of where rural-origin UYDF graduates worked, namely in rural or urban, public or private settings. Methods: An online survey was developed containing questions relevant to the retention of health workers and included: personal satisfaction; hospital resources and employment factors; professional development and support; and community integration, as well as the reasons for working where they do. Of the 317 eligible health science graduates invited to participate, 139 (44%) responded. Descriptive statistics were compiled. Results: Forty-nine percent of graduates were working at a rural public healthcare facility (PHCF), followed by 34% at an urban PHCF, and 11% in the private sector. All the respondents, wherever they worked, reported positively on their work, management support, colleagues, and ability to practise their skills. Graduates working at rural PHCFs reported that patient care was sometimes compromised due to lack of equipment or medicines, with staff shortages being greater than at urban PHCFs. All the graduates reported that they had insufficient time to interact with peers regarding difficult cases, while those at rural PHCFs lacked access to senior staff or specialists compared to those working at urban PHCFs or urban private practice. Lack of professional development opportunities was reported by graduates at rural PHCFs as a reason they may leave, while those at urban PHCFs cited the intention to specialise. Graduates no longer working at a rural hospital reported that the lack of funded posts at rural PHCFs was the main reason (39%), followed by the desire to specialise (29.6%). Graduates working at rural PHCFs cited the 'ability to serve their community' and being 'close to family and friends' as the main reason for working where they do, whereas those working at urban PHCFs cited 'good work experience'. Conclusion: While nearly half of the rural-origin UYDF graduates surveyed continue to work in rural areas, this is considerably less than previously reported, indicating that rural-origin health workers are affected by retention factors. The lack of funded posts at rural PHCFs is a major barrier to the employment and retention of health workers, and to addressing the unequal distribution of health workers between urban and rural PHCFs. This requires commitment from government and other role players to increase the attraction and retention of health workers in rural areas. Focusing on the recruitment of rural students to become health workers, in the absence of adequate retention policies, is insufficient to adequately address shortages of staff at rural PHCFs, as rural-origin graduates will move from rural PHCFs to facilities where they can access these benefits.